Genome sequence of a Spodoptera frugiperda multiple Nucleopolyhedrovirus isolated from fall armyworm (Spodoptera frugiperda) in Nigeria, west Africa - Wennmann, J.; Tepa-Yotto, Ghislain T.; Jehle, J.A.; Goergen, Georg E. (American Society for Microbiology, 2021)
We report the entire genome sequence of an isolate of Spodoptera frugiperda multiple nucleopolyhedrovirus from Nigeria, West Africa. The genome is 132,710 bp long and contains 144 open reading frames. The GC content is 40.3% and, based on baculovirus species demarcation criteria, the isolate belongs to the species Spodoptera frugiperda multiple nucleopolyhedrovirus.